Analisis Akibat Hukum Musnahnya Objek Hak Tanggungan Karena Bencana Alam - Herlin; Ahyuni Yunus; Andi Risma (Qawanin Jurnal Ilmu Hukum, 2020)
This study aims to determine the legal consequences of the destruction of the object of mortgage due to natural disasters and the efforts made by creditors in terms of the destruction of the object of mortgage due to natural disasters. This study uses an empirical method. The research location was carried out at Bank Sulselbar Makassar. Types and sources of data used are primary data and secondary data with data collection techniques, namely field research and library research. The data obtained will be analyzed to produce conclusions and submitted descriptively in order to provide a clear understanding of the results of the research conducted by the author. The results showed that the legal consequence of this incident was the agreement was null and void and the bank suffered a loss because there was no compensation for losses and the efforts made by the creditor were divided into two, namely preventive measures, namely insurance and credit agreement arrangements and repressive measures, namely credit restructuring and litigation or non litigation. To the government of the Republic of Indonesia to review and revise the Mortgage Rights Law and to the bank to pay more attention to the juridical aspects of making credit agreements. So that the settlement of these events has legal certainty.